The Pandora’s box of transparency opened by direct-to-consumer genetic testing - Saruwatari Zavala, Garbiñe (Frontiers in Genetics, 2023)
With the increasing use of direct-to-consumer (DTC) genetic testing, several cases of fertility fraud have been uncovered throughout the world. [METHODS] A review of newspaper articles and specialized literature was made to analyze the issue of fertility fraud. [RESULTS] The most famous cases, some of which are narrated in this article, became a scandal because they were committed by the doctors who treated the patients in question as a routine procedure in their medical practice. Some have been widely exposed in documentaries on streaming platforms, thereby raising awareness about a grave problem. [DISCUSSION] The discussion focuses on the ambiguous regulation on the anonymity of donors, which has been one of the elements of the deception committed against the families using these services. [CONCLUSION] Anonymity nowadays collides with the fascinating Pandora’s box of transparency in genetic information that has been opened by DTC genetic testing.